ONLINE MEDIA ACCEPTANCE AND USE IN INDONESIAN RURAL AREA: PRIMARY SCHOOLS TEACHER’S PERSPECTIVE - Salim, Herli; Hanif, Muhammad (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
Abstract: This exploratory study aimed to describe the current teachers’ acceptance and use of online media for primary school in rural areas.The study used interview and survey as data collection methods which were divided into two focus questions. This study adopted six indicators of Technology Acceptance Model by Davis to measure the participants’ experience on using online learning media. The participants consisted of 30 teachers from four private and government schools in Indonesia. The data collection methods for this study included a survey and open-ended face-to-face interviews in the sense of triangulation for validity and reliability. This study explored the current condition qualitatively, classified each indicator based on interview data reduction and analyzed descriptively. The study found the teachers’ accept using online media in integrated learning but they cannot use it because of the lack facilities and the schools’ rules of using online media. The external variables, perceived ease of use, perceived usefulness and attitudes of the teacher showed the positive acceptance for online learning implementation. Unfortunately, they did not find support to enhance their lack of behavioural intention use and actual use during the teaching practice.The study proposes the development of a supportive environment and facilities to support factual use of online learning in rural areas. This study recognises that online learning was perceived as important to maximize potential of teaching in rural areas. It also highlighted that teachers in rural areas have behavioural intention to implement online learning although in limitation. This study presented significant gap between teachers’ technology acceptance and usage in rural area to be highlighted toward the affordable online learning in the future Keywords: elementary school; teachers’ acceptance; teachers’ use; online media; technology Abstrak: Penelitian eksploratif ini bertujuan untuk mendeskripsikan penerimaan dan penggunaan media online oleh guru saat ini untuk sekolah dasar di pedesaan. Penelitian ini menggunakan metode pengumpulan data wawancara dan survei yang terbagi menjadi dua pertanyaan fokus. Penelitian ini mengadopsi enam indikator Technology Acceptance Model untuk mengukur pengalaman peserta dalam menggunakan media pembelajaran online. Pesertanya terdiri dari 30 guru dari empat sekolah swasta dan negeri di Indonesia. Studi ini menggali secara kualitatif kondisi terkini dan mengklasifikasikan setiap indikator berdasarkan reduksi data wawancara kemudian dianalisis secara deskriptif. Hasil penelitian menemukan penerimaan guru menggunakan media online dalam pembelajaran terpadu tetapi tidak dapat digunakan karena kurangnya fasilitas dan aturan sekolah dalam menggunakan media online. Variabel eksternal, persepsi kemudahan penggunaan, persepsi kegunaan dan sikap guru menunjukkan penerimaan yang positif terhadap pelaksanaan pembelajaran online. Sayangnya, mereka tidak menemukan dukungan untuk meningkatkan kurangnya penggunaan niat perilaku dan penggunaan aktual selama praktik mengajar. Studi ini mengusulkan pengembangan lingkungan dan fasilitas yang mendukung untuk mendukung penggunaan faktual pembelajaran online di daerah pedesaan. Studi ini mengakui bahwa pembelajaran online dianggap penting untuk memaksimalkan potensi pengajaran di pedesaan. Ditegaskan pula bahwa guru di pedesaan memiliki niat berperilaku untuk melaksanakan pembelajaran online meskipun dalam batasan. Studi ini menunjukkan kesenjangan yang signifikan antara penerimaan dan penggunaan teknologi guru di daerah pedesaan untuk disorot ke arah pembelajaran online yang terjangkau di masa depan Kata kunci: sekolah dasar; penerimaan guru; penggunaan oleh guru; media online; teknologi